Correlation between uterine artery Doppler and the sFlt-1/PlGF ratio in different phenotypes of placental dysfunction - Vesna Fabjan-Vodusek; Kristina Kumer; Josko Osredkar; Ivan Verdenik; Ksenija Gersak; Tanja Premru-Srsen (Taylor & Francis Group, 2019)
Objective: To explore correlations between the sFlt-1/PlGF ratio and uterine arteries (UtA) Doppler indexes in placental dysfunction-related disorders (PDD). Methods: We prospectively included women with a singleton pregnancy with preeclampsia (PE) only (n = 22), preeclampsia with fetal growth restriction (FGR) (n = 32), FGR only (n = 12), or normal pregnancy (n = 29). Results: In PDDs, significantly positive correlations between the sFlt-1/PlGF ratio and the mean UtA pulsatility (mPI-UtA), as well as the resistance index (mRI-UtA) were found (p = 0.015, p = 0.019, respectively), but not in normal pregnancies. PDD with signs of impaired placentation, evidenced by the increased sFlt-1/PlGF ratio and mPI-UtA, was found in 50.0%, and, by the increased sFlt-1/PlGF ratio and mRI-UtA, in 65.2%. PDD without signs of impaired placentation, evidenced by the increased sFlt-1/PlGF ratio but normal mPI-UtA, was found in 24.2%, and, by the increased sFlt-1/PlGF ratio but normal mRI-UtA, in 7.6%. A substantial proportion of women with signs of impaired placentation were diagnosed with FGR with or without PE. Conclusion: In PDD, the sFlt-1/PlGF ratio and UtA Doppler indexes increase proportionally. Correlations between the sFlt-1/PlGF ratio and UtA Doppler indexes might help to distinguish between PDDs with and without impaired placentation. However, further studies are needed to explore the correlations in different phenotypes of PDD.